Analysis of the Performance of Phosphorus and Sulphur Co-Doped Reduced Graphene Oxide as Catalyst in Vanadium Redox Flow Battery. Issue 1 (18th January 2022) - Li, Qiang; Wang, Junnan; Zhang, Tianyu; Wang, Zinan; Xue, Zhichao; Li, Jie; Sun, Hong
Abstract : In a vanadium redox flow battery, the traditional polyacrylonitrile based graphite felt (GF) electrode suffers the problems of low electrochemical catalytic activity and low specific surface area. To improve the performance of the GF electrode, we prepared phosphorus and sulphur co-doped reduced graphene oxide (PS-rGO) as catalyst with the simple treatment of reduced graphene oxide (rGO) in the mixture of phytic acid and sulfuric acid. The GF electrode modified with PS-rGO (PS-rGO-GF) was characterized by scanning electron microscope, specific surface area, X-ray photoelectron spectroscopy, cyclic voltammetry, electrochemical impedance spectroscopy, and charge-discharge tests. The PS-rGO-GF shows enhanced performance toward VO 2+ /VO2 + redox reaction. The battery with the PS-rGO decorated GF presents an excellent battery performance with the energy efficiency of 81.37% at the current density of 80 mA cm −2 and the corresponding discharge capacity of 772 mAh due to the high catalytic activity of PS-rGO.